FAKTOR YANG MENYEBABKAN RENDAHNYA PENCATATAAN SIPIL AKTA KELAHIRAN DI DESA PAUH RANAP KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU TAHUN 2011-2012 - Ronal Pranata; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated by the low number of births in the village ownership deed Pauh subdistrict Ranap Peranap Indragiri Hulu.The purpose of this study is to find out what are the factors causing low birth certificate of ownership in the Village Pauh subdistrict Ranap Peranap Indragiri Hulu. The usefulness of this study was to as information for relevant agencies having authority and responsibility in the field of Civil Registration.Types and methods of research used is descriptive research, which can be interpreted as a problem-solving process were investigated by depicting or describing the state of the subject and the object of research at the present time based on the facts that appear or how it is. While the methods used are qualitative research methods to describe the real situation in detail and to see the actual problem and research objectives.The results showed that the presence of some inhibiting factors both from the government and from the public about the ownership of a birth certificate. From the government side of the results of this study concluded that there are still many barriers that prevent the government that takes care of the issuance of birth certificates. So the number of birth certificates in the Village Pauh subdistrict Ranap Peranap Kabupaten Indragiri Hulu is still very low. So is the case of the people in the village Pauh subdistrict Ranap Peranap itself there are also several constraints faced by the public include, lack of public understanding about the importance of having a birth certificate, then the level of education and economic levels of society are still low also cause low birth registration certificate birth.Keyword : Faktors, Civil Registration, Birth Certificates